Irreducible Compositions of Polynomials Over Finite Fields of Even Characteristic - Mehrabi, Saeid M.; Kyuregyan, Melsik K. (Mathematical Problems of Computer Science, 2021)
This note presents some results with the constructive theory of synthesis of irreducible polynomials over a Galois field with even characteristic. We prove a theorem that plays an important role for constructing irreducible polynomials. By this theorem a recurrent method for constructing families of irreducible polynomials of degree n2k (k = 1, 2,…) over F2s is proposed.